(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article analyzes the importance of the development of cognitive processes - attention, memory, perception, thinking and imagination - in the development of speech. The development of cognitive processes through pedagogical and speech therapy methods serves to form children’s speech, communication and creative skills. The article highlights effective methods for the development of cognitive processes - games, experiments, interactive and dramatic activities. At the same time, the speech therapy significance of cognitive processes and their role in preventing speech disorders are emphasized.